From Darkness to a New Dawn: Journey of Rural Women - A Case Study on Mulukanoor Women’s Mutually Aided Milk Producers’ Cooperative Union Limited - Rajanikanth, M. (Indian Journal of Marketing, 2010)
Mulukanoor is a village located in Karimnagar District of Andhra Pradesh, a South Indian State, which is 30 km away from another district’s Headquarter- Warangal. Mulukanoor Cooperative society, a primary agriculture society, was established in that village in the year 1957, and is Asia’s second largest multipurpose cooperative society. It had given inspiration for the formation of Cooperative Development Foundation (CDF) at Hyderabad, the capital of Andhra Pradesh. This CDF has started promoting Thrift cooperatives in Andhra Pradesh. Initially, CDF tried to promote the involvement of women in thrift cooperatives, but found that the men were resistant to this idea. So it started promoting women-only cooperatives in two districts namely Warangal and Karimnagar. In the year 1999-2000, these Women’s Thrift Cooperatives reached new peaks (with savings worth of Rs 21,678,605.). These savings were growing steadily and recorded more than 97% recovery regularly in these Cooperatives for 10 years. With this movement, the members of these societies began to explore several ways of productive investment of their money, as the interest rates were falling and credit absorption was measured in terms of idle cash available with the societies, which included poultry, hand crafts and meat processing. Meanwhile, the area suffered from continuous draught, which led the rural producers to look for new options.